Paediatric Ewing-like sarcoma arising from the cranium – a unique diagnostic challenge. Issue 1 (December 2016) - Robertson, Ian; Bennani, Fadel; Ryan, Ronan; Khan, Waqar; Barry, M.
Abstract Background Paediatric undifferentiated soft tissue sarcomas are a group of tumours that have remained diagnostically challenging. Recently, a subgroup of undifferentiated soft tissue sarcomas with a round to plump spindle cell morphology, expressing theCIC-DUX4 fusion transcript as a result of the t(4;19) or t(10;19) translocation have been identified. Case presentation We describe the first case of aCIC-DUX4 positiveEWSR-1 negative undifferentiated small blue round cell sarcoma arising clinically in the scalp of an eight-year old boy. Our patient presented with a two-month history of a painful swelling in the right parietal region that remained refractory to two courses of antibiotics. On examination, a smooth 30 × 20 mm swelling was palpable in the post-auricular region on the right side. A decision was made to proceed with surgical resection of a likely benign cystic lesion. At surgery, the mass was fixed to the skull and was excised down to the level of the periosteum. Subsequent histology revealed a high-grade undifferentiated small round blue cell tumour, possibly in keeping with a Ewing's sarcoma. Two further specialist paediatric histology opinions were sought, including one from Memorial Sloan Kettering Cancer Center in New York, and these various opinions concluded that the tumour was consistent with the recently described entity ofCIC-DUX4 positiveEWSR-1 negative sarcoma. Conclusions To the best of our knowledge, this is the first case report to describe the presence of this newly classified undifferentiated soft tissue sarcoma within the cranium.